Delicious Destinations: How Food Quality and Location Shape Lifelong Love for Viera Pekanbaru Cake House - Julina, Julina; Prayoga, Ega (International Conference on Business Management and Accounting, 2023)
The purpose of this research is to determine the effect of food quality and location on customer loyalty at Viera Pekanbaru Cake House. The type of research used is quantitative. The population in this study were Pekanbaru people who had purchased at the Viera Pekanbaru Cake House. with a sampling technique using a purposive sampling method totaling 100 respondents. The data analysis technique used in this research is multiple linear regression analysis using the SPSS 23 program. The research results show that partially food quality has a positive and significant effect on customer loyalty, location has a positive and significant effect on customer loyalty. Furthermore, food quality and location simultaneously have a significant influence on customer loyalty at Viera Pekanbaru Cake House. The magnitude of the influence of food quality and location on customer loyalty is 55.9% and the remaining 64.1% is influenced by variables not examined in this research.